Maternal outcome in obstetric ICU and HDU: a study from a teaching hospital in South India - Veerabhadrappa, Vinutha K.; Shivanagappa, Mamatha; Mahadevaiah, Mahesh; Srikanth, Sujatha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The management of critically ill obstetric patients presents a unique challenge. Dedicated High Dependency Unit (HDU) and Intensive Care Unit (ICU) for obstetric patients are widely available in India. The data regarding obstetric critical care is invaluable in formulating policy decisions. The objective is to study the profile of cases admitted to obstetric HDU and ICU and to evaluate maternal outcome and co-morbid conditions. Methods: This was a prospective observational study between January 2017 and June 2018. Results: Total number of obstetric admissions was 7966. Total admissions to obstetric ICU were 60. ICU cases accounted for 0.7% of all obstetric admissions and 1.1% all deliveries. Obstetric cases formed 1.6% of total ICU admissions. Number of admissions to HDU was 576. HDU cases accounted for 7.2 % of all obstetric admissions. HDU utilization rate was 11.32%. Hypertensive disorders of pregnancy (n=22, 33.3%), obstetric haemorrhage (n=18, 30%), septic abortion (n=2, 3.3%) were the most common conditions necessitating admission. Conclusions: Hemorrhage was the most common indication for admission to HDU. Delayed identification and referral were the important obstacles. There is a need for early booking at peripheral centres. Introduction of obstetric ICU and multidisciplinary approach has brought down the incidence of maternal mortality in present centre.